Analysis about management of sadaqah fund at mosques in Shah Alam / Hikmah Abd Rahim, Azri Bhari and Mohd Ashrof Zaki Yaakob - Abd Rahim, Hikmah; Bhari, Azri; Yaakob, Mohd Ashrof Zaki (Academy of Contemporary Islamic Studies (ACIS), 2021)
All institutions, including mosques, have proper financial management. Mosques get resources in a variety of methods, including sadaqah, infaq, zakat, wakaf, and donations from many people. As a result, a mosque is a place that is not only dedicated for worship but also for a number of activities such as lectures, spiritual reminders, and Islamic carnival. Sadaqah fund administration should be systematic for people to try to get benefits from it. The purpose of this study is to examine the types of sadaqah fund management of the various mosques in Shah Alam. This research aims to analyze more about the mosque fund in managing sadaqah funds in Shah Alam. Nowadays, we are all too familiar with problems relating to mosque sadaqah fund management, such as a lack of sadaqah fund management, lack of activity, a lack of sources of income, inefficiency about financial management, and so on. This study was conducted using a qualitative research method, using library and observation method to collect data, including field study and document analysis. The field study will gather information through the interviews from several respondent mosque committees, including mosque officers such as the Imam, Bilal, Treasurer and others that related, while from the document analysis, data and information about mosque fund management will be collected from books, journals, articles, and the internet. The finding showed that different mosques have different types of sadaqah funds but in managing sadaqah funds using similar through the process of the management sadaqah funds. Based on the findings of this study, numerous mosques in Shah Alam will be used as a model for other mosques in managing their sadaqah funds.